The precursors effects on biomimetic hydroxyapatite ceramic powders - Yoruc, Afife Binnaz Hazar; Aydinoglu, Aysu (ELSEVIER, 2017)
In this study, effects of the starting material on chemical, physical, and biological properties of biomimetic hydroxyapatite ceramic powders (BHA) were investigated. Characterization and chemical analysis of BHA powders were performed by using XRD, FT-IR, and ICP-AES. Microstructural features such as size and morphology of the resulting BHA powders were characterized by using BET, nano particle sizer, pycnometer, and SEM. Additionally, biological properties of the BHA ceramic powders were also investigated by using water-soluble tetrazolium salts test (WST-1). According to the chemical analysis of BHA ceramic powders, chemical structures of ceramics which are prepared under different conditions and by using different starting materials show differences. Ceramic powders which are produced at 80 degrees C are mainly composed of hydroxyapatite, dental hydroxyapatite (contain Na and Mg elements in addition to Ca), and calcium phosphate sulfide. However, these structures are altered at high temperatures such as 900 degrees C depending on the features of starting materials and form various calcium phosphate ceramics and/or their mixtures such as Na-Mg-hydroxyapatite, hydroxyapatite, Mg-Whitlockit, and chloroapatite. In vitro cytotoxicity studies showed that amorphous ceramics produced at 80 degrees C and ceramics containing chloroapatite structure as main or secondary phases were found to be extremely cytotoxic. Furthermore, cell culture studies showed that highly crystalline pure hydroxyapatite structures were extremely cytotoxic due to their high crystallinity values. Consequently, the current study indicates that the selection of starting materials which can be used in the production of calcium phosphate ceramics is very important. It is possible to produce calcium phosphate ceramics which have sufficient biocompatibility at physiological pH values and by using appropriate starting materials. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Biocompatibility; Biomimetic; Nanoparticle; Hydroxyapatite; SBF (simulated body fluids); In vitro cytotoxicity; CALCIUM-DEFICIENT HYDROXYAPATITE; NANO-HYDROXYAPATITE; NANOCRYSTALLINE HYDROXYAPATITE; MECHANOCHEMICAL SYNTHESIS; SIZE; NANOPARTICLES; MORPHOLOGY; SODIUM; GLASS; Materials Science